A Prospective Study on the Prescription Pattern of Anti-Cancer Drugs in Breast Cancer Patients - Yadav, Shekhar; George, Jeeva; Ramaiah, Balakeshwa (Indian Journal of Pharmacy Practice)
Background: Cancer is a disease of uncontrolled division of cells in any part of the body. Breast Cancer (BC) is an emerging health issue among female population and accounts for 13% of the death worldwide. The objective of study was to evaluate the drug prescription pattern of BC patients in a tertiary care hospital of Bangalore. Materials and Methods: A prospective observational study was conducted for period of 6 months at a tertiary care hospital. The sampling was performed within day-care unit and in-patient department among BC patients meeting the inclusion criteria. A standard data collection form was designed and used to collect information. Results: A total of 52 patients satisfying inclusion criteria were enrolled in study. Majority of patients were age more than 50 years and in post-menopausal period. Most of the patients were diagnosed with stage IV of BC and were suffering from triple-negative and HER2+tumours. The majority of patients received chemotherapy consists of adjuvant and dual drugs therapy. Most commonly prescribed anti-cancer drugs were paclitaxel (20.18%), cyclophosphamide (18.34%) and carboplatin (14.68%). 59.61% of drugs were prescribed from the National Essential Medicine List (NELM) 2022 and 63.46% from WHO essential drug list 2023. Conclusion: BC is a prevalent type of cancer which needs long term therapy and monitoring to evaluate and refine therapeutic regimen. The present study evaluated the prescription pattern of chemotherapeutic agents among BC patients and promote the rational use of drugs and reduce patient’s sufferings.
Keywords: Breast cancer; Prescription pattern; Anti-cancer drugs; Chemotherapy; Chemotherapeutic regimens; Adjuvant; Neo-adjuvant therapy; WHO; NELM